2022
DOI: 10.3390/ijerph19095539
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Inducing Factors vs. the Risk of Occupational Burnout in the Work of Nurses and Paramedics

Abstract: Introduction: Contemporary healthcare faces new challenges and expectations from society. The profession of a nurse, as well as a paramedic, is essential for the efficient functioning of healthcare. It has its importance not only in promoting and preserving health but also in prevention. With the increasing importance of providing medical care at the highest level, it is expected of these two professional groups to have more knowledge and skills than a few years earlier. The daily contact with patients and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Moreover, a study by Grochowska et al showed that the main stressor among nurses and paramedics is primarily a very high level of responsibility. Nurses are overburdened by excessive demands and shift work and claim that their work is often stressful, leading to physical and mental exhaustion [34]. Dall'Ora et al identified reduced work productivity, poor quality of care, poor patient safety, adverse events, negative patient experiences, medication errors, infections, patient falls, and intent to leave the job among the effects of burnout [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study by Grochowska et al showed that the main stressor among nurses and paramedics is primarily a very high level of responsibility. Nurses are overburdened by excessive demands and shift work and claim that their work is often stressful, leading to physical and mental exhaustion [34]. Dall'Ora et al identified reduced work productivity, poor quality of care, poor patient safety, adverse events, negative patient experiences, medication errors, infections, patient falls, and intent to leave the job among the effects of burnout [21].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study conducted in China found that nurses there who had higher self-esteem characteristics reported less emotional exhaustion, which translated into higher professional performance. The authors concluded that improving coping strategies may be helpful in preventing burnout among nurses, thereby increasing professional effectiveness [34].…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization (WHO) defined stress in workplace as an individual's reaction when work requirements and pressures outreach their skills, abilities and resources, in turn affecting their coping capacities (WHO, 2020). Nurses are exposed to extraordinary occupational stressors such as demanding work shifts (Choi & Kim, 2022; Grochowska et al, 2022), human tragedy and suffering (Taylor, 2019) and bullying behaviours (Foster et al, 2021; Velana & Rinkenauer, 2021). High prevalence of stress among nurses has been discussed in previous studies (Baye et al, 2020; Maharaj et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The intensive patient–healthcare worker relationship in China has burdened the nurses with increased workload ( 68 ). Furthermore, nurses are overburdened by excessive demands and claim that their work is often stressful, leading to physical and mental exhaustion ( 70 ). As a result, some findings call for actions to strengthen communication and organizational support to increase the accomplishment of nurses ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%